Antioxidative constituents from twig and leaves of jasminum sambac / Nurul Fatin Fakhira Mohd Padli ... [et. al.] - Mohd Padli, Nurul Fatin Fakhira; Sulaiman, Siti Nazira; Harun, Aiza; Daud, Shaari; Harith, Siti Suhaila; Abdul Aziz, Noorshilawati (Universiti Teknologi MARA Cawangan Pahang, 2019)
This study aimed to investigate new antioxidative constituents from twig and leaves of Jasminium sambac (Oleaceae family) as potent antioxidant sources. The antioxidant behaviour of each extract from twig and leaves of J. sambac was assessed qualitatively by spraying the thin layer chromatography (TLC) of extracts with 2,2-diphenyl-1-picrylhydrazyl (DPPH) and quantitatively by DPPH radical scavenging method. The collection of antioxidative constituents was carried out using centrifugal chromatography. The chemical structures of all constituents were identified from Gas Chromatography Mass Spectrometer (GCMS). The qualitative Thin Layer Chromatography (TLC) screening of antioxidants showed that all types of extracts from J. sambac leaves demonstrated moderate antioxidant behaviour as well as the extracts from twig parts. The quantitative DPPH radical scavenging activity of leaves and twig extracts revealed dichloromethane (DCM) extract scavenged DPPH free radicals more effective at IC50of 6.24 ppm and 5.22 ppm respectively compared to petroleum ether extract and methanol extract where both extracts exhibited IC50more than 100 ppm. The antioxidative constituents isolated from DCM extract of twig of J. sambac were recognized as isoamyl nitrite and benzophenone whereby benzophenone was also found in DCM extract of J.sambac leaves. Thus, J. sambaccan be considered as a promising source of bioactive compounds with potent antioxidant properties which can be utilized as baseline information to overcome health disorders.